The influence of growth-promoting technologies on the biological structures responsible for cooked meat tenderness - Ebarb, Sara Michelle (Kansas State University, 2015)
The objective of this body of work was to examine effects of growth-promoting technologies (GP) on Longissimus lumborum meat tenderness, focusing on alterations of muscle fiber cross-sectional area (CSA) and collagen solubility. Two studies were conducted and analyzed as randomized complete block designs with repeated measures with GP and day of postmortem aging (DOA) as main effects. Treatments consisted of: a control (CON), implant only (IMP), and implant and [beta]-adrenergic agonist (COMBO). The [beta]-adrenergic agonist utilized for the first was zilpaterol hydrochloride, while the second study examined ractopamine hydrochloride. Objective tenderness of strip loin steaks was measured through Warner-Bratzler shear force (WBSF) after 2 (study 2) or 3 (study 1), 7, 14, 21, or 35 d of postmortem aging. Muscle fiber CSA and collagen solubility were analyzed via immunohistochemistry and hydroxyproline content, respectively. For the first study there was a treatment × DOA interaction (P < 0.01) for WBSF. Compared to CON steaks, IMP steaks had greater (P = 0.01) WBSF on d 3, but were similar (P = 0.21) by d 14. The COMBO steaks remained less tender at all-time points (P < 0.04) except d 21 (P = 0.13) when compared to the CON. Growth-promoting treatment increased the CSA of all three muscle fiber types (P < 0.01), but had no effect on collagen solubility measures (P > 0.21). The second study observed no treatment × DOA interaction (P = 0.54) for WBSF, but GP increased (P < 0.01) WBSF across all DOA. Growth-promoting treatment tended to increase the CSA of type I and IIX fibers (P < 0.10), and increased (P < 0.01) type IIA fiber CSA. In agreement with the first study, there was no treatment × DOA interaction or treatment effect on collagen solubility (P > 0.75). The addition of GP to feedlot heifer production increased WBSF of strip loin steaks and fiber CSA, but did not impact collagen characteristics.
Keywords: Implants; Beta-adrenergic agonist; Beef tenderness; Fiber cross-sectional area; Collagen; Extended aging; Animal Sciences (0475)